Quality of life and coping mechanism among patients with cancer - Thwe, Mon Kyaw. (Universiti Malaysia Sarawak (UNIMAS), 2012)
In consideration of this background, the purpose of this study was to investigate the level of quality of life (QOL) and coping mechanism among cancer patients receiving radiotheraphy and chemotheraphy. Furthermore, the study explores the relation between quality of life (QOL) and coping mechanism in the expectation that the results would serve as useful basic materials for improving the care of such patients.